Observation of a modified superficial layer on heavily loaded contacts under grease lubrication. (June 2021) - Frache, L.; Komba, E. Houara; Philippon, D.; Galipaud, J.; De Barros, M.I.; Douillard, T.; Masenelli-Varlot, K.; Bouscharain, N.; Maheo, Y.; Sarlin, R.; Le Jeune, G.; Berthier, Y.; et al.
Abstract: Several industrial applications require bearings to work under slow oscillating motions and very high contact pressures (aircraft actuators, wind turbine, robotic arms, etc.). Hence, a boundary lubrication regime predominates. However, grease provides the lubrication essential to assure bearing integrity. In this study, the mechanisms involved in protecting the contact surfaces are investigated. High loaded oscillating movements have been applied on a commercial greased deep groove ball bearing. The morphology of its contact was observed using Scanning Electron Microscopy (SEM), revealing superficial transformations. Further, with an extreme surface X-Ray Photoelectron Spectroscopy (XPS) analysis, three cross-sections made by a nanomachining process (FIB) were investigated using Transmission Electron Microscopy (TEM). The analyses revealed a modified layer at the contacts generated by grease interactions. Highlights: Slow oscillations and high contact pressure result to a starve lubrication regime. Greases can provide additives suitable for extremes conditions close to contacts. Thermophysical reactions of additives create solid protective layers in contacts. Multi-technique approach of a stratified modified layer.